LEGISLASI PRODUK HUKUM ISLAM: PROSES, TANTANGAN, DAN IMPLEMENTASI DI INDONESIA - Heriana, Heriana; Hasan, Hamzah; Musyahid, Achmad (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
This article examines the products of Islamic legal thought, which have a broad impact on Muslim communities and can serve as a strong foundation for legal principles. The aim of this study is to explore the existence, issues, and application of Islamic legal instruments within the legal system. The research employs a qualitative method, utilizing bibliometric and textual approaches, along with descriptive analysis.The findings reveal that Islamic law has developed in Indonesia through the products of four schools of legal thought: fiqh (Islamic jurisprudence), fatwas by religious scholars, court decisions (ijtihad), statutory regulations, and sociological legal theories. The challenges in legislating Islamic legal thought in Indonesia include low legal awareness, discrimination, the pluralistic legal system, internal debates among Muslims, lack of education, and political dynamics. Addressing these challenges requires an integrative approach involving all elements of society to foster better understanding and support for the implementation of Islamic law within the national framework.